UNJUK KERJA SISTEM PENTANAHAN TRANSFORMATOR PADA GARDU INDUK 150 KV PT. AMMAN MINERAL NUSA TENGGARA: Transformers Grounding System Performance at PT. Amman Mineral Nusa Tenggara 150 kV Substation - Zyad, Ibnu; Muljono, Agung Budi; Natsir, Abdul (DIELEKTRIKA, 2021)
Short-circuit faults is a faults that must be overcome by protective equipments. One of the protective equipment is a grounding system that serves to reduce the fault current to the ground. The grounding system that will be analyzed in this research is grounding system of the transformer at 150 kV substations PT. Amman Mineral Nusa Tenggara (AMNT) which is then compared to other type of grounding which is gorunding with resistance and reactors in relation to reducing the short circuit current. This research was conducted with a simulation with secondary data from PT. Amman Mineral Nusa Tenggara. The method used is the Newton-Raphson method to obtain power flow in the normal state of the system. Short-circuit fault analysis is carried out in a simulation using ETAP 12.6 Software. The results showed thatthat solid-grounding of the transformer at 150 kV substations PT. AMNT conducts a large fault current. For single line-to-ground faults the magnitude is 2.658 kA at 0% fault distance or at the beginning of the transmission line and this value decreases with the fault distance away from the power plant system. Resistance grounding, whether with low resistance (12 and 40 Ohm) or high resistances (500 Ohm) do not fulfill its grounding requirements. For grounding using a 108 Ohm reactor, the magnitude of single line-to-ground faults is 1,001 kA at 0% fault distance or at the beginning of the transmission line and this value decreases with the faults distance away from the power plant system. This value still fulfill its grounding requirements which is the available ground-fault current should be at least 25% and preferably 60% of the three-phase fault current.